2018
DOI: 10.1186/s12913-018-3780-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Indigenous Australians’ experiences of cancer care: stakeholders’ views on what to measure and how to measure it

Abstract: BackgroundDisparities in cancer outcomes amongst Indigenous Australians reflect a pattern of reduced access to and engagement with health services. A growing emphasis on patient-centred care has increased efforts to measure patient experiences, but it is unclear whether existing approaches: a) assess the most critical aspects of care that shape the experiences of Indigenous people with cancer; and b) facilitate the engagement and participation of Indigenous people with the measurement of care experiences.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
127
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(129 citation statements)
references
References 30 publications
2
127
0
Order By: Relevance
“…There was higher uptake of the online survey completion option by younger age groups compared with older age groups, which is also consistent with a recent qualitative study of Indigenous Australians that suggested older participants prefer paper surveys to online. (24) Explanations of non-response are likely to encompass commonly known barriers in Indigenous health research. Indigenous people have described these, including: a history of exploitative research;…”
Section: Determining the Sampling Frame For The Second Stage Postal Dmentioning
confidence: 99%
“…There was higher uptake of the online survey completion option by younger age groups compared with older age groups, which is also consistent with a recent qualitative study of Indigenous Australians that suggested older participants prefer paper surveys to online. (24) Explanations of non-response are likely to encompass commonly known barriers in Indigenous health research. Indigenous people have described these, including: a history of exploitative research;…”
Section: Determining the Sampling Frame For The Second Stage Postal Dmentioning
confidence: 99%
“…Many challenges exist in the delivery of high quality cancer care in Australia's health system, due to the fragmented nature of cancer services, the length and logistical demands of treatment and sensitivity around diagnosis (15). Focusing on the care experiences of Indigenous people may illuminate issues previously reported as problematic, such as trust and engagement in the health system, (13,15) and facilitate understanding of patients' perspectives in order to guide improvements in care and health outcomes (3,8).…”
Section: Recent Efforts Have Been Made To Consider the Adequacy Of Exmentioning
confidence: 99%
“…Cultural aspects of life are central to Indigenous world views (17,18) and are commonly prioritised above treatment outcomes (19), which contrasts with the disease-oriented approach of the biomedical system. Patient experience measurement instruments may not re ect the world views and priorities of Indigenous people (15), as has been shown regarding supportive care needs (20), health related quality of life (21), wellbeing (22) and social and emotional wellbeing (23). Although there may be some aspects of existing standard measures that are relevant to Indigenous people, their use for Indigenous people presumes common de nitions, values, needs and perceptions of health; a presumption which is often inappropriate (20)(21)(22)(23)(24).…”
Section: Recent Efforts Have Been Made To Consider the Adequacy Of Exmentioning
confidence: 99%
See 2 more Smart Citations